The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jch.12566
|View full text |Cite
|
Sign up to set email alerts
|

Medication Routines and Adherence Among Hypertensive African Americans

Abstract: Poor adherence to prescribed medication regimens remains an important challenge preventing successful treatment of cardiovascular diseases such as hypertension. While studies have documented differences in the time of day or weekday vs weekend on medication adherence, no study has examined whether having a medication-taking routine contributes to increased medication adherence. The purpose of this study was to: (1) identify patients’ sociodemographic factors associated with consistent medication-taking routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 36 publications
5
29
2
1
Order By: Relevance
“…This finding was in line with those of studies done among Africa Americans (77.4%)28 and in northern Ethiopia (73.6%) 29. It was higher than those of studies done in the rural–urban slum areas of Hyderabad (60.6%),30 North India (57.2%),31 Congo-Brazzaville (67.5%),32 a tertiary hospital in Nigeria (44.7%),33 Tikur Anbessa Specialized Hospital in Addis Ababa (69.2%),23 and Adama Referral Hospital in Ethiopia (59.5%) 34.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was in line with those of studies done among Africa Americans (77.4%)28 and in northern Ethiopia (73.6%) 29. It was higher than those of studies done in the rural–urban slum areas of Hyderabad (60.6%),30 North India (57.2%),31 Congo-Brazzaville (67.5%),32 a tertiary hospital in Nigeria (44.7%),33 Tikur Anbessa Specialized Hospital in Addis Ababa (69.2%),23 and Adama Referral Hospital in Ethiopia (59.5%) 34.…”
Section: Discussionsupporting
confidence: 93%
“…8,23,27 In these studies, an increase or decrease in the rate of adherence to the treatment with age may be due to the presence of comorbid chronic diseases, perceived health status, or differences in giving or receiving health care. 7,24 While gender is not a determinant for the rate of adherence to the pharmacological treatment in some studies the adherence rate is high in women in other studies. 8,19 In the present study, although not significant, the rate of adherence was high in women as in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in some studies in the literature, adherence to pharmacological treatment is not associated with socio-demographic characteristics. 7,21,22,26 On the other hand, some studies have indicated that sociodemographic characteristics such as age, gender, level of education, perceived income status are related to adherence to the pharmacological treatment. 3,21,26 For example, while adherence to treatment increases in some studies as the age increases it decreases in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations